2021
DOI: 10.4236/jbm.2021.94010
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Auto-Medication among Pregnant Women in a Conflict Affected, North West Region, Cameroon

Abstract: Background: The excessive use of medicines and generally self-medication is considered as one of the major health and socio-economic problems in different countries. There is increasing evidence that self-medications among pregnant women are common in many developing countries. Despite the adverse impact on pregnancy, there are few programs available for their control. The Northwest region of Cameroon has been affected by socio-political crisis since 2016, which has slowed down economic activities and have gri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
1
Order By: Relevance
“…These findings however contradicted the results reported from a study amongst pregnant women in the Northwest region of Cameroon, which found antiemetics to be the most common drug used for self-medication [24].…”
Section: Discussioncontrasting
confidence: 97%
“…These findings however contradicted the results reported from a study amongst pregnant women in the Northwest region of Cameroon, which found antiemetics to be the most common drug used for self-medication [24].…”
Section: Discussioncontrasting
confidence: 97%
“…The oldest study in terms of publication year ( 2011) is (18). The most recent studies published in 2021 are (2,(19)(20)(21)(22)(23)(24) (Table 1).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The use of medications according to doctor’s prescriptions or instructions has been the subject of several studies. As well, various investigations have pointed to the incidence of self-medication during pregnancy, either in Africa or elsewhere ( Araujo et al, 2013 ; Yimam et al, 2015 ; Cabut et al, 2017 ; Beza, 2018 ; Liao et al, 2018 ; Grover et al, 2019 ; Haque et al, 2020 ; Ake et al, 2021 ; Bobga et al, 2021 ) or worldwide ( Lupattelli et al, 2014 ; Mohseni et al, 2018 ). Health policies, treatment accessibility, and medication distribution regulations are the major factors that make the difference between countries ( Branthwaite and Pechère, 1996 ).…”
Section: Introductionmentioning
confidence: 99%